Textbook as an Element of Didactic Providing of Primary Education in Poland - Motruk, Nadiia (Pedagogical Discourse, 2015)
The article analyzes the main legal documents of Poland of the period of 1999-2009 concerning different kinds of didactic providing of primary school in Poland and, in particular, textbook as the main element of didactic maintenance of educational process in the early stage of school education. In particular, it represents definitional understanding of the term «school textbook», didactic demands to its creation (reflection of the modern state of scientific knowledge, accordance of the didactic apparatus of the study of methodological science, taking into consideration age peculiarities of pupils, proper aesthetic design), the process of approval for school use of textbooks and other subsidiary didactic materials has been analyzes, legal documents, relating to the school textbook in the electronic form have been examined.